Crisis de cantidad y calidad en la universidad peruana - Reluz Barturén, Francisco (2010)
Many researchers have described the outgrowing number of universities around our country as a problem: the higher the quantity, the lower the quality and this applies since there are little academic requirements for students to be enrolled. Students have now become sort of "clients". The author deems this situation as an opportunity for the Peruvian higher education, provided that the State and the civil society device mechanisms of requirements and integrate a working plan aiming towards new and productive relationships between the University and the country.